Ethnicity Situation and Intolerant Attitudes in Multicultural Societies in the Medan City - Erond Litno Damanik (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2020)
This article aims to explore and discuss the phenomenon of intolerant attitudes in multicultural societies. Empirically, the substance of the study is focused on strengthening discrimination and segregation in Medan City. The fundamental problem is formulated in the question: is it true that intolerant attitudes have an impact on discrimination and segregation in multicultural societies? This study was conducted qualitatively with a descriptive approach. Data collected through in-depth interviews and questionnaires. Theoretically, the reference used is the Least-Liked approach developed by Sullivan. Data analysis refers to eight attribute values tolerant according to Ingelhart. The study’s finding is that the Least-Liked attitude is the failure of an assimilationist political mechanism. Multiculturalism is influenced by ethnicity situations that do not guarantee the emergence of multiculturalist attitudes but have the least related effects, discrimination, and segregation. The novelty of this study lies in the idea of multiculturalism which is lacking in the support of assimilative politics. Theoretically, the contribution of this study reinforces Sullivan’s assumptions and empirically emphasizes the importance of assimilative political mechanisms in multicultural societies.